An anion receptor that facilitates transmembrane proton–anion symport by deprotonating its sulfonamide N–H proton. Issue 73 (28th August 2018) - Shinde, Sopan Valiba; Talukdar, Pinaki
Abstract : Indole-based amide-sulfonamide derivatives were synthesized. The X-ray crystal structure and chloride binding studies in solution showed a 1 : 1 stoichiometry. The ion transport study indicated the proton–anion symport across the lipid bilayer membrane. Abstract : Indole-based amide-sulfonamide derivatives were synthesized. The X-ray crystal structure and chloride binding studies in solution showed a 1 : 1 stoichiometry. The ion transport efficiency directly correlated to the p K a of the sulfonamide N–H protons. The mechanistic study indicated proton–anion symport across the lipid bilayer membrane.